Effect of Genotype × Environment interaction for agro-physiological traits in thermo-tolerant early maturing Indian mustard (Brassica juncea L. Czern and Coss) genotypes under heat stress condition: Effect of Genotype × Environment interaction for agro-physiological traits in thermo-tolerant early maturing Indian mustard (Brassica juncea L. Czern and Coss) genotypes under heat stress condition - BHAGIRATH RAM; V V SINGH; K H SINGH; REEMA RANI; M S SUJITH KUMAR; R S JAT; PRIYAMEDHA; H K SHARMA; P K RAI (Journal of Oilseeds Research, 2023)
Brassica juncea is the predominant oilseed brassica in the Indian subcontinent. It accounts for about 80 per cent of the total area under rapeseed-mustard cultivation in India. A study was carried out at the research farm of ICAR-Directorate of Rapeseed-Mustard Research, Bharatpur during rabi 2018-19, 2019-20 and 2020-21 to study effect of Genotype × Environment interaction and genetic variability of early maturing thermo-tolerant genotypes of Indian mustard (Brassica juncea L. Czern & Coss). G x E interaction was significant for all the characters viz., days to flowering, days to maturity, seed yield (kg/ha), membrane stability index (%), excised leaf- water loss (%), relative water content (RWC %), and water retention capacity of leaves (%) except 1000-seed weight. G x E interaction (linear) was also significant for all these eight characters, indicating substantial amount of predictable G x E interaction. Genotype DRMRHT-13-13-5-4 attained minimum days to maturity (122.88) alongwith regression coefficient near to unity and S2 di near to zero considered as stable. While the genotype DRMRHT-13-13-5-5 attained minimum days to maturity (124.44) alongwith regression coefficient near to unity exhibit average stability. Genotype DRMRHT-13-13-5-4, DRMRHT-13-13-5-5 and DRMRHT-13-22-10 could be included in breeding programme where objective is to develop high yielding and heat tolerant stable genotypes over the environment.